Strategic analysis of Porsche AG : luxury EV market - Serhiienko, Yevhenii (2024)
Electric vehicles have become the backbone of sustainable transportation in the rapidly evolving automotive world. The luxury electric vehicle segment, particularly, is seeing significant growth, with high-end manufacturers vying for market dominance. This thesis examines in detail the strategic positioning of Porsche AG, a renowned luxury car manufacturer, in the luxury electric vehicle market. The company's competitive advantages and potential challenges are examined by a comprehensive analysis of Porsche's strategic initiatives. The study uses various strategic tools, including SWOT analysis, Porter's Five Forces, and PEST analysis, to provide a holistic view of Porsche's position in the luxury electric vehicle ecosystem. The thesis concludes with practical recommendations for Porsche AG management to strengthen its position in the luxury electric vehicle segment.